Casino Gambling and the Family: Exploring the Connections and Identifying Consequences. Issue 9 (2nd September 2018) - Anderson, Tammy L.; Rempusheski, Veronica F.; Leedy, Kelly N.
ABSTRACT: Although sanctioned by state governments and widely popular across the United States, gambling remains a controversial activity. For example, casino gambling may be legal and popular, but many believe squandering money is harmful and deviant. People from all backgrounds visit casinos. However, older adults comprise a major portion of the gambling clientele. Along with this have come reports of a wide variety of negative outcomes. Yet, few studies have investigated the relationship between gambling and the family. We use a qualitative in-depth interview grounded theory approach with 34 adults aged 62–88 to investigate the relationship between gambling and family consequences. We explore the impact of gambling on the family with the active aging concept as well as the codependency and sociocultural models of addiction. They offer new ways to understand mild to serious deviance among older adults.